2008
DOI: 10.1016/j.renene.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of a low heat rejection diesel engine operating with biodiesel

Abstract: Vegetable oils are a promising alternative among the different diesel fuel alternatives. However, the high viscosity, poor volatility and cold flow characteristics of vegetable oils can cause some problems such as injector coking, severe engine deposits, filter gumming, piston ring sticking and thickening of lubrication oil from long-term use in diesel engines. These problems can be eliminated or minimized by transesterification of the vegetable oils to form monoesters. These monoesters are known as biodiesel.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(74 citation statements)
references
References 32 publications
7
66
0
1
Order By: Relevance
“…These studies indicate that the fuel consumption is, on average, proportional to the loss of heating values, irrespective of whether heavy-duty or light-duty engines were tested. For example, Hasimoglu et al [37] obtained 13% higher BSFC with a biodiesel having LHV 13.8% lower as compared to diesel on a 4-cylinder, TU and DI diesel engine. [38] found that the BSFC of B100 biodiesel, with a low heating value, 12.9% lower than that of diesel, had increased approximately by 12%, compared to the diesel on a 2.5L, DI and TU, common-rail diesel engine operating at 2400rpm and 64Nm.…”
Section: Brake Specific Fuel Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicate that the fuel consumption is, on average, proportional to the loss of heating values, irrespective of whether heavy-duty or light-duty engines were tested. For example, Hasimoglu et al [37] obtained 13% higher BSFC with a biodiesel having LHV 13.8% lower as compared to diesel on a 4-cylinder, TU and DI diesel engine. [38] found that the BSFC of B100 biodiesel, with a low heating value, 12.9% lower than that of diesel, had increased approximately by 12%, compared to the diesel on a 2.5L, DI and TU, common-rail diesel engine operating at 2400rpm and 64Nm.…”
Section: Brake Specific Fuel Consumptionmentioning
confidence: 99%
“…However, to establish blending and physical properties effects, the blended fuels were prepared by mixing ROB and diesel in different proportions using in tank blending method [37]. Blended fuel has percentage volumetric fraction of 0%, 10%, 20%, 50%, 75% and 100% of Biodiesel and named B0, B10, B20, B50, B75 and B100 respectively.…”
Section: Dynamometermentioning
confidence: 99%
“…The reason for the decreases in power and torque was the lower calorific value of biodiesel (National Biodiesel Board, 2005;CTI -Comitato Termotecnico Italiano, 2013). The increase in BSFC (Utlu and Koçak, 2008;Aydin and Bayindir, 2010) is the result of both the different lower calorific value of biodiesel (hence, of the engine power) and of biodiesel reduced inclination to evaporate compared to diesel oil (Szybist et al, 2007;Haşimoğlu et al, 2008), which is also the cause behind the longer delays in fuel ignition and the changes in the heat release rate and pressure curves (Xue et al, 2011). Figure 2 shows that a biodiesel-fuelled engine has a smokiness that is approximately half of the diesel-oilfuelled engine throughout its entire operative range, due to the higher oxygen content of biodiesel (Murillo et al, 2007).…”
Section: Beginning Of the Experiment: Comparative Tests Between Diesementioning
confidence: 99%
“…Moreover, the engine thermal efficiency does not change and can even improve slightly (Murillo et al, 2007;Raheman and Ghadge, 2007;Szybist et al, 2007;Haşimoğlu et al, 2008;Nabi et al, 2009;Qi et al, 2009;Ryu, 2010;Aybek et al, 2011); however, engine power is reduced (Özkan et al, 2005;Nabi et al, 2009;Qi et al, 2009;Altun, 2011) due to biodiesel lower calorific value and higher viscosity (Szybist et al, 2007;Haşimoğlu et al, 2008). In fact, the viscosity of biodiesel is extremely high at 25 °C, reaching up to 1.6 times the diesel oil viscosity up to 40 °C (Tesfa et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation